Effect of early specialization in team sports. A systematic review - Benítez Fatou, Carlos; Martín Barrero, Alberto; Camacho Lazarraga, Pablo (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
The objective of this research was to find out the impact of sports programmes based on early specialisation on the chances of becoming an expert, the increased likelihood of suffering injuries and/or dropping out of sports practice in the development of young players in team sports. A systematic review was conducted, using the PRISMA statement to study and analyse the field of sport specialisation in team sports. A literature search was conducted in PubMed, ScienceDirect and Web of Science databases, as well as other research sources. Finally, 54 potentially relevant studies were selected. The results indicate that early sport specialisation is linked to high injury rates and a higher risk of sport abandonment, which makes it a hindering element in the development of young athletes. In contrast, a varied sport practice can be a beneficial element for sport development, especially in young subjects whose participation in team sports is deeply linked to the level of interest and motivation they can generate.